Legal Protection and Prevention of Violence Against Children in Family Relations: a Comparative Study at the Religious Court and the Bandung City Police Department - Hopipah, Eva Nur; Khosyi’ah, Siah (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Cases of domestic violence against children continue to increase over time, including within the family sphere. According to information derived from the PPA Symphony of the Ministry of Women's Empowerment and Child Protection, as of the initial quarter of 2023, Bandung City ranks third in terms of the highest incidence of violent cases in West Java. As many as 37 reports of acts of violence were recorded in the city of Bandung in approximately two months. So the focus regarding this matter must be paid more attention by the various parties concerned in terms of legal protection and prevention. This research uses a comparative method with the aim of comparing the Bandung Religious Court in its civil scope and the Bandung Police in terms of criminal acts. What are the preventive steps and resolution of domestic violence cases against children within the family in the city of Bandung? And the results, when compared between PA and Bandung Police, have varying data due to different absolute and relative competencies. However, in general, domestic violence cases against children in the city of Bandung are more often resolved criminally, rather than civilly, in terms of fighting over child custody after divorce.